2013
DOI: 10.1021/ja307077f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights on the ortho-Hydroxylation of Aromatic Compounds by Non-heme Iron Complex: A Computational Case Study on the Comparative Oxidative Ability of Ferric-Hydroperoxo and High-Valent FeIV═O and FeV═O Intermediates

Abstract: ortho-Hydroxylation of aromatic compounds by non-heme Fe complexes has been extensively studied in recent years by several research groups. The nature of the proposed oxidant varies from Fe(III)-OOH to high-valent Fe(IV)═O and Fe(V)═O species, and no definitive consensus has emerged. In this comprehensive study, we have investigated the ortho-hydroxylation of aromatic compounds by an iron complex using hybrid density functional theory incorporating dispersion effects. Three different oxidants, Fe(III)-OOH, Fe(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
94
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 178 publications
(73 reference statements)
18
94
0
Order By: Relevance
“…Theoretical studies of such biomimetic models may not only identify the key elements that determine their chemical reactivities, but may also provide insight into intermediates and reactivities of parent enzymes (Shaik et al, 2007a; de Visser et al, 2013). To date, DFT calculations have been applied extensively to various types of non-heme iron species (Scheme 1) (Bassan et al, 2002, 2005a,b; Roelfes et al, 2003; Decker and Solomon, 2005; Kumar et al, 2005; Quinonero et al, 2005; Berry et al, 2006; Bernasconi et al, 2007, 2011; de Visser, 2006, 2010; Hirao et al, 2006a, 2008a,b, 2011; Rohde et al, 2006; Decker et al, 2007; de Visser et al, 2007, 2011; Johansson et al, 2007; Noack and Siegbahn, 2007; Sastri et al, 2007; Sicking et al, 2007; Bernasconi and Baerends, 2008, 2013; Comba et al, 2008; Dhuri et al, 2008; Fiedler and Que, 2009; Klinker et al, 2009; Wang et al, 2009a, 2013b; Cho et al, 2010, 2012a, 2013; Geng et al, 2010; Chen et al, 2011; Chung et al, 2011b; Seo et al, 2011; Shaik et al, 2011; Vardhaman et al, 2011; Wong et al, 2011; Ye and Neese, 2011; Gonzalez-Ovalle et al, 2012; Gopakumar et al, 2012; Latifi et al, 2012; Mas-Ballesté et al, 2012; McDonald et al, 2012; Van Heuvelen et al, 2012; Ansari et al, 2013; Kim et al, 2013; Lee et al, 2013; Sahu et al, 2013; Tang et al, 2013; Ye et al, 2013; Hong et al, 2014; Sun et al, 2014). The intriguing reactivity patterns of these complexes are the result of active involvement of electrons in d-type MOs, which gives rise to multi-state scenarios (Shaik et al, 1998; Schröder et al, 2000; Schwarz, 2011).…”
Section: Applications Of Dftmentioning
confidence: 99%
“…Theoretical studies of such biomimetic models may not only identify the key elements that determine their chemical reactivities, but may also provide insight into intermediates and reactivities of parent enzymes (Shaik et al, 2007a; de Visser et al, 2013). To date, DFT calculations have been applied extensively to various types of non-heme iron species (Scheme 1) (Bassan et al, 2002, 2005a,b; Roelfes et al, 2003; Decker and Solomon, 2005; Kumar et al, 2005; Quinonero et al, 2005; Berry et al, 2006; Bernasconi et al, 2007, 2011; de Visser, 2006, 2010; Hirao et al, 2006a, 2008a,b, 2011; Rohde et al, 2006; Decker et al, 2007; de Visser et al, 2007, 2011; Johansson et al, 2007; Noack and Siegbahn, 2007; Sastri et al, 2007; Sicking et al, 2007; Bernasconi and Baerends, 2008, 2013; Comba et al, 2008; Dhuri et al, 2008; Fiedler and Que, 2009; Klinker et al, 2009; Wang et al, 2009a, 2013b; Cho et al, 2010, 2012a, 2013; Geng et al, 2010; Chen et al, 2011; Chung et al, 2011b; Seo et al, 2011; Shaik et al, 2011; Vardhaman et al, 2011; Wong et al, 2011; Ye and Neese, 2011; Gonzalez-Ovalle et al, 2012; Gopakumar et al, 2012; Latifi et al, 2012; Mas-Ballesté et al, 2012; McDonald et al, 2012; Van Heuvelen et al, 2012; Ansari et al, 2013; Kim et al, 2013; Lee et al, 2013; Sahu et al, 2013; Tang et al, 2013; Ye et al, 2013; Hong et al, 2014; Sun et al, 2014). The intriguing reactivity patterns of these complexes are the result of active involvement of electrons in d-type MOs, which gives rise to multi-state scenarios (Shaik et al, 1998; Schröder et al, 2000; Schwarz, 2011).…”
Section: Applications Of Dftmentioning
confidence: 99%
“…Both Fe IV (O) and Fe V (O) species were proposed as active oxidants in the absence of direct spectroscopic evidence. 620 …”
Section: Introductionmentioning
confidence: 99%
“…Calculations suggested that part of the reason for the low reactivity of triplet Fe IV (O) was because of steric clash between the incoming aromatic substrate and the equatorial ligands, which blocked access to the key π * acceptor orbitals on the Fe IV (O) unit. 6,7,25,32 …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, an Fe II complex may be oxidised to Fe III and then coordinate H 2 O 2 . The resulting Fe III hydroperoxido complexes themselves are known to be strong oxidants [98] but may also produce ferryl species and OH radicals (homolytic cleavage of the O-O bond). [99,100] Moreover, coordination of H 2 O 2 to the Fe II precursor and subsequent homolytic cleavage of the O-O bond may lead to an Fe IV (OH) 2 complex, a tautomer of the reactive ferryl complex.…”
Section: Relevant Oxidation Reactionsmentioning
confidence: 99%